2021
DOI: 10.3390/jcm11010154
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Extent of Pain Is Associated with Pain Intensity, Catastrophizing and Some Measures of Central Sensitization in People with Frozen Shoulder

Abstract: The aim of this cross-sectional study was to explore the spatial extent of pain and its association with clinical symptoms, psychological features, and pain sensitization in people with frozen shoulder (FS). Forty-eight individuals with FS completed pain drawings (PDs) and reported their clinical symptoms including pain intensity (Visual Analogue Scale) and shoulder disability (Shoulder Pain and Disability Index). Moreover, pain sensitization measurements (pressure pain thresholds, temporal summation, conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Previous studies have reported that the pain of FS is recurrent and frequently progresses to the chronic stage. Pain catastrophizing is considered a negative mental set during anticipated or actual painful experiences and has been shown to be increased in FS patients ( 9 ). As for pain vigilance, the PVAQ has been demonstrated to be a reliable instrument for the evaluation of vigilance and attention to pain ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the pain of FS is recurrent and frequently progresses to the chronic stage. Pain catastrophizing is considered a negative mental set during anticipated or actual painful experiences and has been shown to be increased in FS patients ( 9 ). As for pain vigilance, the PVAQ has been demonstrated to be a reliable instrument for the evaluation of vigilance and attention to pain ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research, however, suggests that the pathophysiology of FS is complex, and central pain mechanisms have a crucial role in patients with FS ( 8 12 ). According to Mercè et al FS patients experience more extended areas of pain, which is associated with higher levels of pain, pain catastrophizing, and pain sensitization ( 9 ). Furthermore, Michel et al also observed greater allodynia, hyperalgesia, catastrophizing, and hypervigilance in FS patients compared to healthy participants, indicating potential central sensitization for pain in FS ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, recent research has shown that central pain mechanisms also have a crucial role in patients with AC. 4,24,25 Furthermore, patients with AC are at an increased risk of poor mental health due to persistent Sponsorships or competing interests that may be relevant to content are disclosed at the end of this article. J. Li, R. Zhao, C. Wang, and J.…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, recent research has shown that central pain mechanisms also have a crucial role in patients with AC. 4 , 24 , 25 Furthermore, patients with AC are at an increased risk of poor mental health due to persistent pain. 5 Research indicated that individuals enduring prolonged pain frequently manifest symptoms of depression, with as many as 85% of those grappling with chronic pain being affected by severe depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Tiene alta prevalencia en la sociedad, con un impacto significativo en la calidad de vida de las personas (Bilbeny et al, 2018). Adquiriendo importancia en las evaluaciones de salud, como medida de bienestar centrada en la percepción personal respecto a metas, expectativas, normas y preocupaciones según el estado de salud físico-mental, grado de independencia y relación socio-ambiental de la persona (Martínez & Calvo, 2014); debido a que el dolor crónico puede producir alteración en la funcionalidad de la vida diaria, kinesiofobia, catastrofización, deterioro en las relaciones interpersonales, aislamiento, complicaciones a nivel laboral, discapacidad e incluso invalidez (Bilbeny, 2019;Balasch et al, 2021).…”
Section: Introductionunclassified